Intravenous Paclitaxel Is Specifically Retained in Human Gynecologic Carcinoma Tissues In Vivo. Issue 4 (1st April 2009) - Koshiba, Hisato; Hosokawa, Kenichi; Mori, Taisuke; Kubo, Akiko; Watanabe, Ai; Honjo, Hideo
Abstract : Paclitaxel and carboplatin are commonly used and well-tolerated agents for gynecologic malignancies. The persistence of platinum in human tissues for 14 days and the long-term retention of platinum in tissues for up to 17 months have been reported. Paclitaxel remains in human uterine cervical cancer tissues for 6 days. These findings prompted us to determine the retention of paclitaxel and carboplatin in human uterine cervical carcinoma, endometrial carcinoma, ovarian carcinoma, and pelvic lymph nodes to establish baseline parameters and guide the development of more effective treatment interventions. Thirty patients with uterine or ovarian carcinomas were treated with intravenous weekly paclitaxel-carboplatin chemotherapy before surgery. The concentrations of these agents in carcinoma tissue, normal cervical, myometrial and ovarian tissues, and pelvic lymph nodes were measured 5 days after the final administration. Paclitaxel was specifically retained in cervical, endometrial, and ovarian carcinoma tissues but was not detected in lymph nodes. In contrast to paclitaxel, carboplatin was readily detectable with similar levels in all tumor-associated and normal host tissues. In addition, a low paclitaxel concentration in cervical carcinoma tissue was significantly associated with short progression-free survival and overall survival. Further studies are needed to clarify the tissue distribution of anticancer drugs in humans and promote optimal treatment strategies enhancing paclitaxel lymphatic targeting.